Changes in DNA methylation associated with a specific mode of delivery: a pilot study - Krumpolec, Patrik; Kodada, Dominik; Hadžega, Dominik; Petrovič, Oliver; Babišová, Klaudia; Dosedla, Erik; Turcsányiová, Zuzana; Minárik, Gabriel (Frontiers in Medicine, 2024)
Background The mode of delivery represents an epigenetic factor with potential to affect further development of the individual by multiple mechanisms. DNA methylation may be one of them, representing a major epigenetic mechanism involving direct chemical modification of the individual’s DNA. This pilot study aims to examine whether a specific mode of delivery induces changes of DNA methylation by comparing the umbilical cord blood and peripheral blood of the newborns. Methods Blood samples from infants born by vaginal delivery and caesarean section were analysed to prepare the Methylseq library according to NEBNext enzymatic Methyl-seq Methylation Library Preparation Kit with further generation of target-enriched DNA libraries using the Twist Human Methylome Panel. DNA methylation status was determined using Illumina next-generation sequencing (NGS). Results We identified 168 differentially methylated regions in umbilical cord blood samples and 157 regions in peripheral blood samples. These were associated with 59 common biological, metabolic and signalling pathways for umbilical cord and peripheral blood samples. Conclusion Caesarean section is likely to represent an important epigenetic factor with the potential to induce changes in the genome that could play an important role in development of a broad spectrum of disorders. Our results could contribute to the elucidation of how epigenetic factors, such as a specific mode of delivery, could have adverse impact on health of an individual later in their life.